Comparison of Productivity of Sentul and Kampung Chickens until the Age of 3 Months in the First Generation Selection Population (G1) - Wahyuni Wahyuni; Depison Depison; Gushariyanto Gushariyanto (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
This study aimed to compare the productivity of Sentul chickens and first-generation Kampung chickens (G1) until the age of 3 months. The research material were Sentul chicken and Kampung chicken. The method used was an experiment method or direct observation with a sample of 174 chickens from each strain. The data collected were egg weight, doc weight, body weight, body weight gain, body measurements, and selection response. Data on egg weight, body weight, and body measurements were analyzed using the average difference test (t-test), while the average value vector of body measurements Sentul chicken and Kampung chicken were analyzed using the T2-Hotelling statistical test. To identify the body size and body shape characteristics of Sentul chickens and Kampung chickens were analyzed using principal component analysis. Data processing used the statistical software Minitab version 18. The results of this study showed that egg weight, body weight at the age of DOC-3 months and body measurements of Sentul chickens were significantly different (P<0.05) higher than the Kampung chickens. This study concludes that the egg weight, body weight, body weight gain, and body sizes of Sentul chickens are higher than Kampung chickens. The size characteristic of Sentul and Kampung chickens is chest circumference. The characteristic of the shape of the Sentul chicken is the length of the wings, while the shape of the native chicken is the width of the chest. The selection response and the heritability value of the Sentul chickens was higher than Kampung chikens.